Relationship between lipoprotein B and the severity of coronary microvascular dysfunction - Yang, Lili; Zhang, Jingjing; Han, Jiangyan; Jiang, Xiaojuan (Clinical and experimental hypertension (1993), 2025)
Contributing factors for the development of heart failure (HF) involve both apolipoprotein B (ApoB) and coronary microvascular dysfunction (CMD). Although ApoB has been linked to diverse cardiovascular risks, its association with CMD remains unclear. A total of 145 patients undergoing cardiac single-photon emission computed tomography (SPECT) scan was enrolled into this retrospective study. Based on ApoB serum level, all subjects were classified into three groups (Group 1-3). Myocardial flow reserve (MFR) was calculated using myocardial blood flow (MBF) tested in different contexts. ApoB serum level was positively correlated to rest MBF but inversely associated with stress MBF and MFR. Following adjustment for covariates, a significant relationship was observed between increased ApoB and decreased MFR. The predictive value of ApoB was test by Receiver Operating Characteristic Curve (ROC) analysis, showing an area under curve (AUC) of 0.87. The findings indicated that a higher level of ApoB correlated with the severity of CMD.